Direct conversion of carboxylic acid to olefins over Pt-loaded, oxygen-deficient alkali hexatitanate catalysts with ketonization-hydrogenation-dehydration activity - Promchana, Pratya; Boonchun, Adisak; T-Thienprasert, Jiraroj; Sooknoi, Tawan; Maluangnont, Tosapol (My University, 2021)
The production of long chain olefins from fatty acids via decarbonylation is limited by low olefins selectivity at high conversion. Here, we reported the direct acid-to-olefins conversion via the ketonization-hydrogenation-dehydration sequence at 400 °C and atmospheric 10 %H2/Ar. The oxygen vacancy defects (VO) were essential in acetic acid ketonization over the oxygen-deficient alkali hexatitanate A2Ti6O13-x (A[dbnd]K, Na and Li) catalysts, as evidenced from the activity of reduced vs non-reduced catalysts. The presence of VO was deduced spectroscopically with XPS and DRUV-VIS, and the ease of VO formation was ranked via the DFT calculations. The ketonization activity was proportionated to the square of the VO content (x2), consistent with the bimolecular reaction mechanism. The Pt-loaded K2Ti6O13-x enabled the direct acid-to-olefins transformation as shown by a complete conversion of two model compounds (heptanoic acid and lauric acid) with ∼30–40 % yield of long chain olefins. Heptanoic acid (C7) underwent ketonization to 7-tridecanone (a C13 ketone) prior to the hydrogenation-dehydration to 7-tridecene, a C13 olefin. The strong metal-support interaction (SMSI) between Pt and K2Ti6O13-x inhibited further hydrogenation of the olefin to a low-value alkane. For lauric acid (C12), 12-tricosene (a C23 olefin) was produced analogously. The catalytic activity and products selectivity over Pt-loaded K2Ti6O13-x significantly depended on the Pt content (0–1.0 wt%). The simultaneous C[sbnd]C coupling and oxygen removal prior to the subsequent hydrogenation and dehydration is a potential approach toward the production of long chain olefins with the (2n-1) carbon atoms from Cn-fatty acids.
Keywords: Alkali hexatitanate; DFT calculations; Ketonization; Long chain olefins; Platinum